Toward universal access to information: an analysis of digital accessibility policy readiness in U.S. public universities - Emmanuel Kwame Cudjoe; Phylix Akorfa Asilevi (Universal Access in the Information Society, 2026)
Abstract This study examines how U.S. public universities are developing institutional digital accessibility initiatives in response to the Department of Justice’s (DOJ) April 2024 ADA Title II mandate. Using a qualitative content analysis, guided by the Technology–Organization–Environment (TOE) framework, the study analyzes publicly documented digital accessibility policy readiness from the 2026 U.S. News & World Report top 20 U.S. public universities. Data was collected from official university websites using a systematic search strategy and archived to support transparency. A two-level analytical approach was employed, consisting of institution-level analyses of the TOE factors, followed by cross-institutional synthesis to identify patterns. A structured TOE-based codebook was applied, and inter-coder reliability was assessed using Holsti’s coefficient, yielding strong agreement overall (C.R. = 0.91). Technologically, the findings indicate consistently high levels of digital accessibility readiness across institutions. All twenty (20) universities explicitly adopted WCAG 2.1 AA, with three (3) committing to WCAG 2.2 AA. This is supported by the widespread deployment of accessibility implementation, evaluation, remediation, and monitoring tools, despite variations in inter-operability and STEM content accessibility, suggesting areas for continued development. Organizational readiness was evidenced by intense training initiatives, dedicated newly established accessibility offices and governance structures including new/revised formal accessibility policies. Environmental readiness is driven by explicit recognition of federal and state legal obligations, public accountability expectations, and external partnerships. The study concludes offering implications for advancing inclusive access to information as U.S. public universities move toward full ADA Title II digital accessibility compliance.